Analisis Yuridis Pasal 66 Ayat (1) Undang-Undang Jabatan Notaris Terhadap Pengawasan Notaris - Qurratu Uyun Ramadani Zulkhainen (Officium Notarium, 2022)
This research departs from the large number of application data submitted to the Constitutional Court (Mahkamah Konstitusi, MK) regarding Article 66 paragraph (1) of Law no. 30 of 2004 on the Position of Notary and its amendments by Law no. 2 of 2014 (Undang-Undang Jabtasn Notaris, UUJN). At least since UUJN was promulgated, there have been 4 MK decisions related to this article, and the most recent is PMK No.16/PUU-XVII/2020. Application regarding Article 66 paragraph (1) UUJN regarding the phrase "...with the approval of the Notary Honorary Council". Hence the position of a notary seem to need redefinition considering this particular article is ceaselessly appealed to the Constitutional Court with an unconstitutional argument (i.e. it fails to fulfill the principle of equality before the law). Therefore, the formulation of the problems studied are: first, what is the authority of the Honorary Council of Notaries regarding the granting of approval in the judicial process for Notaries?; and second, is Article 66 paragraph (1) UUJN contradicting the principle of equality before the law? This is a normative legal research with statutory and conceptual approaches. The results of this study conclude that the first notary summoned by the investigator must obtain approval from the Honorary Council of Notaries to be summoned and examined before the investigator; and secondly Article 66 paragraph (1) UUJN is not a form of conflict with the principle of equality before the law.Key Word: Authority, Honorary Council of Notaries, Principle of Equality Before the Law AbstrakPenelitian ini berangkat dari banyaknya data permohonan yang diajukan ke Mahkamah Konstitusi (MK) perihal Pasal 66 ayat (1) UU No. 30 Tahun 2004 tentang Jabatan Notaris beserta perubahannya sebagaimana UU No. 2 Tahun 2014 (UUJN). Setidaknya sejak UUJN diundangkan, sudah ada 4 putusan MK terkait pasal ini, dan yang termuktahir adalah PMK No.16/PUU-XVII/2020. Permohonan mengenai Pasal 66 ayat (1) UUJN berkenaan dengan frasa “...dengan persetujuan Majelis Kehormatan Notaris”. Betapa jabatan notaris seakan memerlukan redefinisi sehingga satu pasal ini selalu dimohonkan ke MK dengan argumen inkonstitusional (tidak memenuhi prinsip equality before the law). Oleh karena itu, rumusan masalah yang diteliti adalah: pertama, bagaimana kewenangan majelis kehormatan Notaris terkait pemberian persetujuan dalam proses peradilan bagi Notaris?; Kedua, apakah Pasal 66 ayat (1) UUJN bertentangan dengan prinsip persamaan derajat di hadapan hukum? Penelitian ini merupakan penelitian hukum normatif dengan pendekatan perundang-undangan dan konseptual. Hasil penelitian ini menyimpulkan, pertama Notaris yang dipanggil oleh penyidik harus memperoleh persetujuan dari MKN untuk dipanggil dan diperiksa di hadapan penyidik; dan kedua Pasal 66 ayat (1) UUJN adalah bukan bentuk pertentangan dari prinsip equality before the law.Kata-kata Kunci: Kewenangan, Majelis Kehormatan Notaris, Prinsip Persamaan di Hadapan Hukum